Retrieval practice improves learning in children with diverse visual word recognition skills. Issue 10 (26th November 2019) - Moreira, Bruna Fernanda Tolentino; Pinto, Tatiana Salazar da Silva; Justi, Francis R. R.; Jaeger, Antônio
ABSTRACT: A large body of research shows that performing tests is more beneficial for the retention of studied materials than restudying those materials, a phenomenon termed "testing-effect". A contemporary debate on the testing effect literature concerns whether the benefits of tests are equivalent for individuals with different cognitive skills, as the capacity to decode written words, for example. In the current study, we approached this issue in two experiments by examining whether testing is equally beneficial for children with diverse visual word decoding skills. To achieve this goal, we recruited sixth and fourth grade children (experiments 1 and 2, respectively) and administered a reading aloud task to assess their visual word recognition skills, and administered a memory task about an encyclopedic text to promote the testing effect. Memory for the restudied/tested contents of the encyclopedic text were probed after a seven-day interval, and although children from both experiments showed robust testing effects, such effects were not associated with their visual word decoding skills. These findings suggest that children with diverse word decoding skills can be benefited by retrieval practice.